Motor Skill, Motor Planning, and Motor Performance in Adults with Severe Mental Illnesses and Obesity. Issue 4 (13th June 2022) - Gill, Simone V.; Ayoub, Maria J.; Mueser, Kim T.; McGurk, Susan R.
Abstract: Motor functioning in persons with serious mental illness (SMI) is not well studied. We assessed motor functioning in people with SMI ( n = 15) vs. adults with obesity ( n = 15) and healthy controls ( n = 15). Motor skills were assessed using balance and coordination tests. Motor planning and performance were assessed in Obstacle and Metronome Walking Tasks. The SMI group scored lower on balance and coordination tests (all ps < 0.001), and took longer steps when approaching obstacles (all ps < 0.001), but had unimpaired motor performance on the Metronome Walking Task. In obesity, excess body mass impairs motor skills, which adversely impacts motor performance. In persons with SMI, motor performance was unimpaired, with cognitive and neuroanatomical abnormalities likely underlying balance, coordination, and motor skill challenges.